2017
DOI: 10.1161/circep.117.005407
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Substrate and Triggers of Paroxysmal Atrial Fibrillation in Patients With Obstructive Sleep Apnea

Abstract: Background Obstructive sleep apnea (OSA) is associated with atrial remodeling, atrial fibrillation (AF), and increased incidence of arrhythmia recurrence following pulmonary vein isolation (PVI). We aimed to characterize the atrial substrate, including AF triggers in patients with paroxysmal AF (PAF) and OSA. Methods and Results In 86 patients with PAF (43 with ≥ moderate OSA [apnea-hypopnea index ≥15] and 43 without OSA [apnea-hypopnea index <5]) right atrial (RA) and left atrial (LA) voltage distribution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 24 publications
0
58
0
3
Order By: Relevance
“…With the burden of AF increasing at rates greater than those predicted by known risk factors, there has been interest in several newer risk factors [107], including obesity, sleep apnoea, physical inactivity and prehypertension [30,[108][109][110][111]. These risk factors have now been demonstrated to result in change to the atrial myocardium and remodelling that favours the development and maintenance of AF [18][19][20]24,[112][113][114]. Several studies have characterised the atrial substrate for arrhythmia in these conditions, and reported similar findings to those seen with the various cardiac risk factors [16,22,23,27].…”
Section: Detection and Management Of Newer Risk Factorsmentioning
confidence: 99%
“…With the burden of AF increasing at rates greater than those predicted by known risk factors, there has been interest in several newer risk factors [107], including obesity, sleep apnoea, physical inactivity and prehypertension [30,[108][109][110][111]. These risk factors have now been demonstrated to result in change to the atrial myocardium and remodelling that favours the development and maintenance of AF [18][19][20]24,[112][113][114]. Several studies have characterised the atrial substrate for arrhythmia in these conditions, and reported similar findings to those seen with the various cardiac risk factors [16,22,23,27].…”
Section: Detection and Management Of Newer Risk Factorsmentioning
confidence: 99%
“…21 The rationale for universal OSA assessment of those who are undergoing PVI for AF is clearly supported by the following: (1) the strong biologic plausibility shown by experimental data confirming the role of OSA-induced intermittent autonomic nervous system fluctuations and impact of intrathoracic pressure alterations on the thin-walled atria; (2) ability to reverse recognized risk factors for AF recurrence, such as hypertension, which has a strong evidence base for improvement with OSA treatment; and (3) consistent findings from many studies with pooled estimates showing a 42% reduction of AF recurrence in those with OSA who are treated with CPAP vs those who are not treated after PVI. 19,20 The following domains identified by existing literature support Hill's tenants of causality of OSA and AF (ie, strong magnitude of association, biologic plausibility, and longitudinal association supporting temporality). This combined with the high prevalence and burden of OSA in this patient population provides a strong and compelling basis for the broad standardized assessment of OSA in patients with AF undergoing PVI.…”
mentioning
confidence: 86%
“…18 Recent data support that although the pulmonary veins are the major triggers for AF in OSA, extrapulmonary vein triggers are also commonly present, and ablation of these triggers may improve clinical outcomes compared with PVI alone. 19 For example, in a clinicbased study, among those with both OSA and AF who underwent direct current cardioversion, those who used CPAP therapy had a lower 12-month recurrence of AF compared with those without AF (42% vs 82%, P ¼ .013), with further analyses demonstrating that those with a greater degree of untreated nocturnal hypoxia were most susceptible to this increased AF recurrence. 16 Furthermore, a meta-analysis focused on examination of the impact of CPAP treatment in OSA in those undergoing catheter ablation showed a 42% decreased risk of AF (RR, 0.58; 95% CI, 0.47-0.70) in those treated with CPAP with greatest benefit in those were younger, obese, and male 20 and had consistent findings in other aggregate data.…”
mentioning
confidence: 99%
“…Mesmo após a correção para fatores de risco em comum, ambas as patologias são preditores de risco independentes entre si. 36,37 A presença de AOS gera um ambiente propício para a ocorrência de arritmias atriais. 38,39 Repetidos episódios de hipoventilação associados a despertares resultam em ativação de mediadores inflamatórios, dano celular secundário à hipóxia e hiperativação simpática.…”
Section: Fibrilação Atrial E a Apneia Obstrutiva Do Sonounclassified
“…Microscopicamente, o remodelamento estrutural da cavidade atrial caracteriza-se por hipertrofia e disfunção dos miócitos atriais, desorganização das junções intercelulares (gap junctions) 36 , reexpressão de proteínas (rediferenciação) 81 e reativação do programa de genes fetais. 82 Esta última representa o retorno à via glicolítica, na tentativa de preservar o miócito disfuncionante, neste caso devido à sobrecarga pressórica.…”
Section: Remodelamento Atrial Microscópicounclassified